Visible Boys, Invisible Girls: The Representation of Gender in Learn English with Tito (A Critical Discourse Analysis of English Language Textbooks for Primary School) - Antiksari, Nadia Tiara (Universitas Pendidikan Indonesia, 2011)
ABSTRACT: This study, entitled â€œVisible Boys, Invisible Girls: The Representation of Gender in Learn English with Tito (A Critical Discourse Analysis of English Language Textbooks for Primary School)â€, is aimed at revealing the representation of gender in a series of Indonesian primary school English textbooks which are published by PT. Mutiara Permata Bangsa, Yogyakarta in 2007. The study is also aimed at gaining information about the editorâ€™s perspective upon the issue and investigating the underlying ideology behind the representation. This research employs the framework of Critical Discourse Analysis (CDA). The main data are six textbooks for primary school. This study also conduts an inteview with the book editor. The text analysis utilizes transitivity system of Halliday which focuses on investigating Participants, Processes, and Circumstances of a clause. It is supported by lexical choise analysis of the text and a qualitative analysis of the interview. The findings show that the books favor males than females. Male characters are more visible in that they occur dominantly and they appear to hold more important roles of Participant. In terms of Gender stereotyping, males are perpetually associated with a more well-paid jobs i.e. â€˜doctorâ€™ and â€˜pilotâ€™ for male characters and â€˜teacherâ€™ for femalesâ€™. Meanwhile, females are more likely valued by their physical appearance and personality i.e. â€˜slimâ€™, â€˜fair-skinnedâ€™, â€˜beautifulâ€™, â€˜kindâ€™, and diligentâ€™. At the end of the research,Â the editor admitted the lack of concern on the issue of gender in composing her textbooks. These seem to indicate male domination as the underlying ideology behind the representation. Â